Aggressive Fibromatosis versus Low Grade Fibrosarcoma - a Diagnostic Dilemma - Sikka, Seema (International Journal of Pathology, 2018)
The fibromatosis are a group of lesions that can infiltrate widely, replacing muscle, fat and bone with fibrous tissueof varying cellularity. They do not develop distant metastases, however, locally they show an aggressive andinfiltrative behaviour. The major challenge in the diagnosis lies in not over or under diagnose of fibrosarcoma andan underdiagnosis of reactive fibrosis. But this histologic differentiation is necessary owing to different treatmentstrategies